Peran Inspiratif Elzatta Hijab dalam Mendorong Peningkatan Penggunaan Busana Muslim di Kota Bandung - Nurrasyid, Akbar Dwi; Fauziah, Sumainah (Universitas Gajah Putih, Indonesia, 2023)
This article discusses the role of the Elzatta Hijab brand in increasing the use of Muslim fashion in the city of Bandung. Elzatta Hijab has created inspiring fashion trends and blended modern designs with traditional values ​​in Muslim fashion. Through effective marketing strategies, including the use of social media, participation in events, collaboration with designers, as well as the existence of physical stores and online platforms, Elzatta Hijab has succeeded in influencing the trend and use of Muslim fashion in the city of Bandung. The impact of using the Elzatta Hijab Muslim dress on the religious and cultural identity of the people of Bandung City is also significant, with the strengthening of religious identity, respect for local wisdom, and adaptation in Muslim dress traditions. In conclusion, Elzatta Hijab has made a positive contribution in increasing the use of Muslim clothing in the city of Bandung and strengthening community identity.